برنامج تدريبي مقترح من أجل تحسين مستوى التفكير الخططي لدى لاعبي كرة القدم أقل من 19 سنة - بودهري, عبدالرحمن; تاجموت, عبدالجبار (My University, 2020)
ملخص الد ا رسة بالعربية: اثر البرنامج التدريبي المقترح في تطوير مستوى التفكير الخططي لدى لاعبي كره القدم اقل من 19 س نة: هدفت هذه الد ا رسة الى التعرف على اثر البرنامج التدريبي المقترح في تطوير وتحسين مستوى التفكير الخططي لدى لاعب ك رة القدم بحيث اردنا العمل على عينة قوامها 24 لاعب ك رة القدم اقل من 19 س نة من فريقين وداد جيلالي بن عمار واتحاد والابطال, الواقع 10 لاعبين مثلوا المجموعة التجريب ية 14 لاعبا مثل المجموعة الضابطة و اردنا استخدام المنهج الوصفي لتلائمه مع طبيعة الد ا رسة مع استخدام المعالجات الاحصائ ية المتوسط الحسابي والانح ا رف المعياري , تحليل التباين. ولكن كم نتمكن من ذلك نظ ا ر لظروف ومعانات التي عشناها في ايام الاخيرة وذالك بسبب الوباء الذي فرض على السلطات قيام بالحجر الصحي وعليه نقوم بالاستدلال وإتباع النتائج التي اظهرتها الد ا رسات السابقة بحيث ان استخدام ب ا رمج تدريب ية وعقل ية له اثر رجعي وايجابي على تطوير مستوى التفكير الخططي ولذلك ت وصي الد ا رسات السابقه بضرو رة اهتمام المدربين والباحثين بتطوير ب ا رمج تدريب ية تاكتكية وعقل ية. The effect of the proposed training program in developing the level of tactical thinking among football players under 19 years: This study aimed at identifying the impact of the proposed training program in developing and improving the level of tactical thinking of the football player so that we wanted to work on a sample consisting of 24 footballers under 19 years of two teams, Widad Jilali bin Ammar and the Federation and Champions, the reality that 10 players represented the experimental group 14 For players such as the control group, we wanted to use the descriptive approach to fit it with the nature of the study with the use of statistical treatments, arithmetic mean, standard deviation, and variance analysis. But how much we can do that, given the circumstances and suffering that we lived in the last days, and that is because of the epidemic that imposed on the authorities the practice of quarantine, and therefore we infer and follow the results shown by previous studies so that the use of training and mental programs has a positive and retroactive effect on developing the level of tactical thinking and therefore studies recommend The preceding is that trainers and researchers should pay attention to developing tactical and
MES2020-15
Keywords: البرنامج التدريبي; التفكير الخططي; كره القدم